Effects of a Molecular Monolayer Modification of NiO Nanocrystal Layer Surfaces on Perovskite Crystallization and Interface Contact toward Faster Hole Extraction and Higher Photovoltaic Performance. (2nd March 2016) - Bai, Yang; Chen, Haining; Xiao, Shuang; Xue, Qifan; Zhang, Teng; Zhu, Zonglong; Li, Qiang; Hu, Chen; Yang, Yun; Hu, Zhicheng; Huang, Fei; Wong, Kam Sing; et al.
Abstract : NiO is a promising hole transporting material for perovskite solar cells due to its high hole mobility, good stability, easy processibility, and suitable Fermi level for hole extraction. However, the efficiency of NiO‐based cells is still limited by the slow hole extraction due to the poor perovskite/NiO interface and the inadequate quality of the two solution‐processed material phases. Here, large influences of a monolayer surface modification of NiO nanocrystal layers with ethanolamine molecules are demonstrated on the enhancement of hole extraction/transport and thus the photovoltaic performance. The underlying causes have been revealed by a series of studies, pointing to a favorable dipole layer formed by the molecular adsorption along with the enhanced perovskite crystallization and the improved interface contact. Comparatively, the solar cells based on a diethanolamine‐modified NiO layer have achieved a rather high fill factor, indeed one of the highest among NiO‐based perovskite solar cells, and high short‐circuit photocurrent density ( J sc ), resulting in a power conversion efficiency of ≈16%, most importantly, without hysteresis. Abstract : Diethanolamine (DEA) modification of the thin NiO film surface in perovskite solar cells enhances the interfacial hole extraction rate and thus the photovoltaic performance. Perovskite film quality and the contact at the perovskite/NiO interface are greatly improved through the chemical coordination of Ni and Pb with the –NH– and –OH groups of DEA, respectively.